ANALYSIS OF TECHNIQUES AND TECHNOLOGIES FOR INTRA SOIL APPLICATION OF ORGANIC FERTILIZERS PREPARATION OF SOIL FOR SOWING - T Махамов Х.; Р.Х., Товашов (International Journal of Psychosocial Rehabilitation, 2020)
The article provides an analysis of techniques and technologies for the application of organic fertilizers in the preparation of field melons for planting.